Farm characteristics and management routines related to cow longevity: a survey among Swedish dairy farmers - Alvåsen, Karin (Acta Vet Scand, 2018)
BACKGROUND: Longevity is an important trait for increasing the profitability of dairy production. Long cow longevity is also essential to reduce the environmental impact of milk production, and to maintain positive consumer attitude. Genetic selection for increased longevity has been effective, but the phenotypic trend of longevity in Swedish dairy cows has not been improved. The objective of this study was to identify herd characteristics and management routines that are associated with the average cow longevity in a herd. To obtain this information, a questionnaire was developed and sent out to 661 Swedish dairy farmers. RESULTS: The response rate was 35%. Seventeen of the 62 characteristics investigated had either a univariable association with the outcome (days from birth to culling) at P < 0.15, or were identified as confounders in the causal diagram and were therefore considered as candidates for the multivariable analysis. Multiple imputation was used to fill in the missing data from the questionnaires, and this increased the number of usable observations in the multivariable modeling from 156 to 228. Only a few of the investigated herd characteristics and management routines were associated with average cow longevity. The results demonstrated that using herd health advisory services shortened the average longevity, while using breeding advisory services prolonged the average longevity in the herd. Furthermore, having a greater interest in animal breeding (i.e. genetic selection) decreased the longevity, and calling the veterinarian when discovering an unhealthy cow increased the average longevity. Higher age of the farmer was also associated with longer average herd longevity. CONCLUSIONS: The herd average cow longevity was only associated with some of the farm characteristics and management routines studied. The results demonstrate that the use of advisory services and farmers’ attitudes could be targeted for increasing the herd longevity. Further, the results indicate that other e.g. qualitative factors influencing farmers’ decisions play an important role. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13028-018-0390-8) contains supplementary material, which is available to authorized users.